Effectiveness of Skytrex Adventure as a therapeutic avenue for physical activities in reducing visitors’ stress level - Raman, Thivya Laxshmy (2019)
The adequacy of nature in decreasing stress through enjoyment exercises is yet to be deductively and thoroughly assessed. In Malaysia, there is still a lack of research on the association between forest and outdoor recreation in relation to stress reduction. The purpose of this study is to measure the effectiveness of outdoor recreation on visitors’ stress level at Skytrex Adventure Shah Alam, Selangor, which is situated in the forest of Taman Botani Negara, Shah Alam. This study was conducted through administration and distribution of questionnaire forms to 150 respondents. The respondents were requested to complete the questionnaire before and after undergoing high rope course at Skytrex Adventure, Shah Alam. Prior to that, the respondents, who had agreed to participate in the study, were briefed on the experiment. Generally, the psychometric questionnaire consists of Profile of Mood States (POMS), Positive and Negative Affect Schedule (PANAS), Restoration Outcome Scale (ROS) and Perceived Stress Scale (PSS). These tests were used to identify the psychological effects of outdoor recreation in nature setting. Results indicated that the PANAS evaluation showed a highly significant increase (p<0.001) in the positive attitudes among the respondents after undergoing the high rope course, and a significant reduction (p<0.01) in the scores for negative attitudes. In addition, the POMS test also showed a significant difference (p<0.001) in the Total Mood Disturbance among the respondents after taking part in the high rope course. This finding indicates that the respondents felt more restored and thus showed a reduction in tension and anxiety, depression, anger, as well as confusion moods. However, there is a significant increase (p<0.01) in the respondents’ level of fatigue after undergoing the high rope course.